AKIBAT HUKUM KONVERSI HAK ATAS TANAH ULAYAT DALAM PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP DI KABUPATEN SAMOSIR - Andrews Peatalun Napitupulu, (2022)
Land is an inherent and most important natural resource so that its existence is very dependent on human life, and in the end the reciprocal relationship between land and humans cannot be avoided. In most areas of Samosir Regency, you can still find customary law communities who manage, administer and control ulayat lands in accordance with the provisions and regulations of local customary law. On the basis of upholding legal certainty and protection for the local customary law community, the first land registration was carried out for communal land with the aim of obtaining a certificate for the land. This desire is also supported by the issuance of the Regional Regulation of Kab. Samosir No.1 of 2020 concerning Indigenous Community Rights (Law) of the Batak Toba Samosir custom. Registration of customary land is also in line with the government's land registration program, namely Complete Systematic Land Registration (PTSL). In this research will bring the formulation of the problem how to regulate the conversion of land rights, the process of conversion and determination of the subject of the land and the legal consequences of the conversion of customary land through the PTSL program